2000
DOI: 10.1139/w00-080
|View full text |Cite
|
Sign up to set email alerts
|

A common molecular signature unifies the chitosanases belonging to families 46 and 80 of glycoside hydrolases

Abstract: The 3D structure-oriented alignment of the primary sequences of fourteen chitosanases, mainly of bacterial origin and belonging to families 46 and 80 of glycoside hydrolases, resulted in the identification of the following pattern common to all these enzymes: E-[DNQ]-x(8,17)-Y-x(7)-D-x-[RD]-[GP]-x-[TS]-x(3)-[AIVFLY]-G- x(5,11)-D. This pattern is proposed as the molecular signature of the chitosanases from families 46 and 80. It includes several amino acids essential for enzyme activity and (or) stability as sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2002
2002
2022
2022

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…The structure-based alignment of the primary sequence of CsnN174 with the other members of GH46 family revealed that the arginine residue at position 42 is conserved in all the chitosanases biochemically characterized [17] strongly suggesting that this arginine plays an important role in catalysis [3]. This arginine is listed in the molecular signature of glycoside hydrolase families 46 and 80 [10] in the PROSITE database [29]. …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The structure-based alignment of the primary sequence of CsnN174 with the other members of GH46 family revealed that the arginine residue at position 42 is conserved in all the chitosanases biochemically characterized [17] strongly suggesting that this arginine plays an important role in catalysis [3]. This arginine is listed in the molecular signature of glycoside hydrolase families 46 and 80 [10] in the PROSITE database [29]. …”
Section: Resultsmentioning
confidence: 99%
“…The structural features of CsnN174 are not only shared by GH46 members, but also by GH22, GH23 and GH24 lysozymes, as well as GH19 chitinases, all members of the “lysozyme superfamily” [2,6-9]. This list could be extended toward GH80 family based on primary sequence similarities [10]. …”
Section: Introductionmentioning
confidence: 99%
“…Thus far, much less is known about the metabolic pathway of chitosan, although many kinds of chitosanolytic enzymes from various organisms have been identified and their tertiary structure of proteins has been determined (Tremblay et al 2000). Thus far, much less is known about the metabolic pathway of chitosan, although many kinds of chitosanolytic enzymes from various organisms have been identified and their tertiary structure of proteins has been determined (Tremblay et al 2000).…”
Section: Diversity Of Chitinases and Chitosanasesmentioning
confidence: 99%